Self-Regulated Learning for Active Organizational Students of the Faculty of Psychology and Humanities - Lestari, Veranika Dwi; Az Zahra, Aning (Universitas Muhammadiyah Yogyakarta, 2024)
University students should have extensive knowledge and abilities (skills), character, and vision that are more advanced than ordinary people. Student activities such as organizations can be a place for students to develop their abilities. Students are also required to have good time management so that academic achievement and organizational activities can run in balance. This study aims to determine self-regulated learning in the aspects of active organizational students with high academic achievement. The study focused on self-regulated learning in active organizational students at the Faculty of Psychology and Humanities. This research uses a descriptive qualitative approach. The method in this study used in-depth interviews, and the participants in this study were two people. This study found information on self-regulated learning aspects, including cognitive regulation, motivational aspects, and behavioral aspects. The study results show that active student organizations that apply self-regulated learning can control behavior, maintain achievement, and have many relationships and experiences not obtained in lecture classes.